Building bridges for refugees: toward a typology of bridging organizations - Lawrence, Thomas B.; Hardy, Cynthia (1998)
In this article, the authors examine the dynamics of bridging organizations in activist domains. The purpose of these organizations is to serve as a link between other organizations and individuals. Drawing on a comparative case study of three national refugee systems, they develop a typology of bridging organizations based on the degree to which each organization shares the values of other organizations in the domain: center extension, border federation, pure bridge. The center extension shares the values of center organizations, transmitting them to the border. The border federation operates much closer to the border, voicing its values and negotiating on its behalf with the center. The pure bridge is a classic bridging organization: It attempts to incorporate values from both center and border, mediating, translating, and negotiating them in an attempt to connect the two sides in a workable relationship. - Reproduced
Keywords: Organizations